Perilaku Penderita Hipertensi di Rumah Sakit X - Yasinta Indah Sulistyaningrum; I Wayan Artana; Alfiery Leda Kio (Nursing News : Jurnal Ilmiah Keperawatan, 2021)
The prevalence of hypertension is still high, despite various treatments have been done. The success of hypertension treatment depends on the behavior of people with hypertension during treatment. This study aimed to understand the behavior of hypertensive sufferers at X Hospital which supported or unsupported the health. The qualitative study with phenomenology method was involved six informants. Data collection was done by in-depth interviews, observation, and analysis based on Miles Huberman principals. This research found the behaviors that support the health of hypertension sufferer's are the application of a low salt diet, cessation of cigarette and alcohol consumption, increase in activity and exercise, regulation of sleep and rest needs, application of stress control methods, and hypertension treatment and care. Overall, the informants have implementesd that six behaviors, but in the aspects of treatment and care of hypertension it has not been implemented properly. It is hoped that the nurses in the hospital need to provide education about healthy lifestyle independently that able to lower hypertension and emphasize on the importance of undergoing regular treatment and care to health services